Upaya Guru Dalam Meningkatkan Keterampilan Sosial Peserta Didik Kelas IV SDN Banjaranyar 04 - Triputra, Dedi Romli; Zahwa, Akillatuz; Toharudin, Moh (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to describe: (1) Teachers' efforts to improve social communication skills. (2) The teacher's efforts in improving social skills help. (3) The teacher's efforts to improve empathy social skills. In this study, researchers used a qualitative research type using a phenomenological approach. The research will be carried out from February 2023 to July 2023. The subjects in this research are students and teachers. Data collection techniques through passive participant observation, semi-structured interviews and documentation. Data validity uses source and data triangulation. Data analysis uses Miles and Huberman theory using the steps of data collection, data reduction, data presentation and drawing conclusions. The results of research on teacher efforts to improve social communication skills are carried out through solving conflict problems in subject matter as well as problems in real life, so teachers can accustom students to actively ask questions and express opinions in teaching and learning activities. The teacher's efforts to improve social skills in building groups are carried out through group discussions, puzzle games, picket scheduling so as to foster an attitude of cooperation, responsibility, discipline and respect for opinions. The teacher's efforts in improving social skills in solving problems are carried out through story problems with the teacher giving students questions or problems to be solved, instructing participants to be directed towards themselves as people who have problems and looking for solutions, instructing students to solve problems independently and learn responsibility .